Relationship between Respiratory Tract Complaints, Functional Status, and Smoking in Hairdressers, Auto Painters, and Carpenters - Ümran Toru; Peri Meram Arbak; Kezban Özmen Süner; Özlem Yavuz; Naciye Karataş (The Scientific World Journal)
Background and Aim. It was observed that occupation and smoking increased each other’s effects on the development of airway diseases. We aimed to search the relationship between respiratory symptoms, smoking, and occupation. Materials and Methods. 225 employees in Düzce, Turkey, were applied a survey questioning respiratory complaints, pulmonary function tests (PFTs) and cotinine measurements in urine. Results. Cough (26.7%), phlegm (30.7%), and chest tightness (21.3%) were encountered more in carpenters compared to other groups and phlegm was statistically higher at significant level compared to other groups. The complaints of cough (30.4%), phlegm (27.4%), and chest tightness (21.5%) were significantly higher in individuals whose cotinine level was above 500 ng/mL and forced expiratory volume in one second (FEV1)/forced vital capacity (FVC) ratio, maximum midexpiratory flow rate (MMFR) values were significantly lower. Dyspnea complaint of auto painters whose cotinine level was below 500 ng/mL was significantly higher and also expected MMFR% value of this group was significantly lower compared to other groups. While age had independent effect on respiratory function tests, type of the job was found to be independently effective on MMFR. Conclusion. Smoking increases respiratory complaints of employees. In auto painters, the occupation causes airway disease regardless of smoking.